The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.1590/s1519-69842012000300008
|View full text |Cite
|
Sign up to set email alerts
|

Functional diversity, soil features and community functioning: a test in a cerrado site

Abstract: Community functioning may be affected by functional diversity, which measures the extent of complementarity in resource use. We tested whether there was a relationship between functional diversity of woody species and community functioning on a fine scale, using FD as a measure of functional diversity and litter decomposition rate as a surrogate for community functioning. We measured eight functional traits from a woodland cerrado community in southeastern Brazil. Then, we tested the correlation between FD and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 44 publications
0
6
0
Order By: Relevance
“…Quantifying changes in these traits is important to understand the patterns of species distribution and to predict vegetation responses to environmental changes (Silva and Batalha, 2009;Freitas et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Quantifying changes in these traits is important to understand the patterns of species distribution and to predict vegetation responses to environmental changes (Silva and Batalha, 2009;Freitas et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Other studies show this positive correlation between biomass/wood stock and functional diversity (TILMAN et al, 1996;LOREAU et al, 2001;CARDINALE et al, 2007;ZENG et al, 2012;CONTI;ROSCHER et al, 2013;RUIZ-BENITO et al, 2014). Nonetheless, Freitas et al (2012) have not identified significant relationship between the two variables when they were evaluating the effects of functional diversity on decomposition rate of woody assembly in cerrado sensu stricto. However, it is important to evaluate the effects of functional diversity in small scale, once that they can reveal more details about the mechanism of subjacent biologic stand (WIENS, 1989).…”
Section: Discussionmentioning
confidence: 94%
“…As most part of Europe lies in the northern temperate climate zone, current conclusions and recommendations regarding functional diversity and conservation tend to be less suitable to ecosystems from outside that climate. Because tropical species communities are prone to be more complex (Janzen, 1975;Vamosi et al, 2006), relationships between ecosystem functioning and functional diversity in the tropics may not be as straightforward, as is usually assumed (Freitas et al, 2012;Martins and Batalha, 2006). Testing hypothesis in tropical ecosystems would contribute to expanding the current understanding of functional diversity in conservation strategies' applicability.…”
Section: Discussionmentioning
confidence: 99%